Transition Modeling and Econometric Convergence Tests - Phillips, Peter C. B.; Sul, Donggyu (Econometrica, 2007)
The copyright to this Article is held by the Econometric Society. It may be downloaded, printed and reproduced only for educational or research purposes, including use in course packs. No downloading or copying may be done for any commercial purpose without the explicit permission of the Econometric Society. For such commercial purposes contact the Office of the Econometric Society (contact information may be found at the website http://www.econometricsociety.org or in the back cover of Econometrica). This statement must the included on all copies of this Article that are made available electronically or in any other